Effects of sheep grazing on legume composition and production in a Mediterranean grassland in Central Greece - Platis P.D.; Papachristou T.G.; Tsiontsis A.I.; Papanastasis V.P. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In a Mediterranean grassland of Central Greece, dominated by annual species and grazed throughout the winter and spring (November to May) with sheep, an area of 0.1 ha was fenced out and compared with an adjacent grazed one of similar size for three consecutive years. It was found that legumes were represented only by four annual species, namely Medicago minima, Trifolium subterraneum, T. nigrescens and T. glomeratum. Despite this low number, however, their biomass was making more than 50 per cent of the total production in the ungrazed plot while overgrazing resulted in its significant reduction. Moreover, the results indicate that legumes were affected not only by sheep grazing but also by the extreme weather conditions in the winter months.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)